The Influence of Distributed Leadership on Effective School Governance and Improved School Performance - Al Hassanieh, Rima (2020)
The Distributed Leadership Theory states that the success of an organization cannot depend on one person alone. It gives staff at various levels the power and autonomy to create change, aiming to utilize the skills, ideas and initiatives of the entire organization. The purpose of this research is to identify the impact of distributed leadership on school governance, leading to an improvement in the overall school performance. This study was conducted in two private schools in Al Ain. The existing literature was analyzed to understand the concept of distributed leadership and the challenges faced by the school hierarchy. The data was collected using a mixed method research approach, i.e. both surveys and interviews were conducted. The data was then analyzed using descriptive analysis and moderated regression analysis. The conclusion reached was that DL has a positive impact on the relationship between governance and performance. It was also found that DL was being applied in both schools at varying levels, and each had areas that needed improvement. The most important implication was the connection of distributed leadership to governance and performance. This study has the potential to be beneficial not only to the schools studied, but the other schools of the region as well.